A SOSIALISASI TERKAIT ALAT PELINDUNG DIRI (APD) DAN SAFETY SIGN KEPADA SISWA SERTA PENYERAHAN ALAT PEMADAM API RINGAN (APAR) DI SMKN 4 PPU - Nofan, Nofansyah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Real Work Lectures are a form of community service by going directly to the field carried out by students accompanied by field supervisors. In providing serving to Sesulu Village, an outreach was carried out and the delivery of fire extinguishing aids was carried out. The aim of the service carried out is to increase student’s awareness of the risk of danger wherever we are, as well as handing over Light Fire Extinguishers to the SMK Negeri 4 PPU School.